An integrated approach to explore the monophyletic status of the cosmopolitan genus Hexabathynella (Crustacea, Bathynellacea, Parabathynellidae): two new species from Rottnest Island (Wadjemup), Western Australia. Issue 1 (31st December 2023) - Perina, Giulia; Camacho, Ana; Cooper, Steven J.B.; Floeckner, Stephanie; Blyth, Alison J.; Saccò, Mattia
Abstract : The Hexabathynella genus is the only genus of the family Parabathynellidae that has supposedly a worldwide distribution. Currently, there are 23 species described from five continents. In Australia, only two Hexabathynella species have been named from the eastern coast, however, a few taxa have been collected from Western Australia during stygofauna sampling as part of research studies and legislated compliance-based Environmental Impact Assessments. One of these areas includes Rottnest Island (Wadjemup), located offshore of Perth in Western Australia. Unpublished data on stygofaunal communities inhabiting the groundwater of the island refer to discrete abundances of copepods and syncarids, but no species description has been carried out. In this study, we describe two new species: Hexabathynella quokkai and H. bisetosa, expanding the characterization of the subterranean aquatic community at Rottnest Island, and using a COI, 18S and 12S sequence-based phylogeny to test the monophyletic status of the genus. Our findings shed new light on the distribution of Hexabathynella and its reported cosmopolitan distribution. http://zoobank.org/urn:lsid:zoobank.org:act:03634EAD-4D27-4446-AE53-4248303D5020 http://zoobank.org/urn:lsid:zoobank.org:act:1B325914-90FD-471E-AC03-20741C7C925A